Bromatological characterization of Moringa oleifera foliage in different development stages - Y. Méndez (Revista Cubana de Ciencia Agrícola, 2018)
Using a random block design with four replications, the effect of regrowth age (60, 90, 120, 150 and 180 days) on the bromatological composition of Moringa oleifera foliage was evaluated in both seasons. The sampling took place in plots of 0.5 ha, to which a uniformity cut of one meter above the soil, without irrigation or fertilization, was applied. Contents of dry matter, crude protein, neutral detergent fiber, acid detergent fiber, acid detergent lignin, cellulose, hemicellulose, cellular content, P, Ca, ashes and organic matter were determined. An analysis of variance according to the experimental design was applied. Crude protein decreased with age in both seasons, showing significant differences among all ages. The best values were obtained at 60 days of regrowth (22.79 and 24.05 % in rainy and dry periods, respectively). A similar performance was demonstrated by dry matter digestibility, metabolizable energy and total digestible nutrients, while neutral detergent fiber increase with age with the highest values at 180 days (34.41 and 31.97 % in rainy and dry periods, respectively). It was evident that with the increase of plant maturity, there is a decrease of its nutritional quality, mainly due to the increase of neutral detergent fiber and acid detergent lignin, and decrease of crude protein, dry matter digestibility and total digestible nutrients, among other aspects. It is suggested to study lower regrowth ages, as well as biomass yields and secondary metabolites.